Mengukur Tingkat Laba dalam Pengelolaan Piutang - Machmud, Mulyana; A. Yayuk Sri Rahayu, Ersa Mayora, Siti Sarah Alyasah-Gan, Andi Ruslan Abdullah, (Pascasarjana STIE Amkop Makassar, 2025)
The purpose of this study is to find out the management of PT. Pos Indonesia (Persero) Parepare Branch and its influence on the profit level of PT. Pos Indonesia (Persero) Parepare Branch for the period 2011 – 2015. The management of data from the Financial Statements, namely the Balance Sheet Report for the period 2011-2015 and the Profit and Loss Statement for the period 2011-2015 at PT. Pos Indonesia (Persero) Parepare Branch. The analysis methods used are Receivables Turnover Ratio and Profitability Ratio. Based on the results of the research that has been carried out, it shows that the management of receivables at PT. Pos Indonesia (Persero) Parepare Branch is less effective, and the relationship between receivables management and profitability level at PT. Pos Indonesia (Persero) Parepare Branch has a very strong relationship. Kata Kunci: Receivables Management, Receivables Turnover, Profitability, Profit Level.